2018
DOI: 10.5709/acp-0246-4
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning and Reading in Adults. A New Reasoning Task for Detecting the Visual Impendance Effect

Abstract: The visual impedance hypothesis states that at the time of reasoning, the reading context provokes visual images, which may add irrelevant details to an inference and thus could hamper reasoning. This study aims to create a new visual version of a reasoning task, similar to the traditional propositional task of relational syllogisms, but based on visuospatial components. Using such a task, it would be possible to investigate the deductive ability of relational inferences in tests without the need for reading. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…It was expected that reasoning would not be affected by literacy skills. This study with adults without any RD (Panagiotidou et al, 2018) showed that the new pictorial task was similar to the traditional propositional task used to measure transitive reasoning with simple problems and to detect the visual impedance effect (in the imaginable invalid difficult problems of the pictorial task), showing that this task was also useful to detect this effect (Authors, 2018). The absence of the impedance effect in adults with RD strongly indicates that they are processing transitive inferences in a different way that could be related to difficulties in reading (Bacon & Handley, 2010, 2014.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…It was expected that reasoning would not be affected by literacy skills. This study with adults without any RD (Panagiotidou et al, 2018) showed that the new pictorial task was similar to the traditional propositional task used to measure transitive reasoning with simple problems and to detect the visual impedance effect (in the imaginable invalid difficult problems of the pictorial task), showing that this task was also useful to detect this effect (Authors, 2018). The absence of the impedance effect in adults with RD strongly indicates that they are processing transitive inferences in a different way that could be related to difficulties in reading (Bacon & Handley, 2010, 2014.…”
Section: Introductionmentioning
confidence: 88%
“…A pilot study was performed that aimed at assessing whether the pictorial/visual reasoning task using pictures instead of written protocols, designed in a previous investigation with adult participants (Panagiotidou et al, 2018), could be used with a child population at primary school level.…”
Section: Pilot Experimentsmentioning
confidence: 99%
See 3 more Smart Citations